Clinico-etiological profile and ultrasonographic evaluation of recurrent abdominal pain in children aged 5 years and above - G., Nayak Dhavalkumar; Bamnawat, Subhash; Goyal, Dileep (International Journal of Contemporary Pediatrics, 2021)
Background: Recurrent abdominal pain (RAP) is very common and the most troublesome health related issue in school aged children affecting up to 10-20%, but very rare below 5 years and above 15 years. Objective of this study was to assess clinico-etiological profile and ultrasonographic finding in children with recurrent abdominal pain at tertiary care hospital in southern Rajasthan. Methods: This prospective observational study was carried out at tertiary care hospital Udaipur, from January 2019 to June 2020. Total 57 children aged 5 years and above who fulfilled the Apley’s criteria for recurrent abdominal pain were enrolled. Patient’s detailed history and physical examination including detailed per abdominal examination were recorded on pre-structured Performa. All patient underwent for routine investigation which consists of complete blood count, urine routine and microscopy with culture, stool examination and USG of abdomen and pelvis. Results: Mean age of children with recurrent abdominal pain in this study was 9.9 years with SD±2.86 with male to female ratio was 1.28:1. Out of 57 children, organic cause was found in 21 (36.84%) children and in 36 (63.16%) children no organic cause was found for recurrent abdominal pain. Most common organic cause was urinary tract infection in 8 (38.09%) children. Total 19 (33.33%) children had mesenteric lymphadenopathy on ultrasonography, out of which organic cause was present in 10 (52.64%) children and no cause was found in 9 (47.36%) children (p value>0.05). Conclusions: Recurrent abdominal pain might occur either due to organic or non-organic causes. Urinary tract infection is one of the most common organic cause in this study. Mesenteric lymphadenopathy was the most common ultrasonography finding in children presented with recurrent abdominal pain.